Electrochemical Detection of Nitrite Based on Iron Oxide–Reduced Graphene Oxide Nanocomposite Modified Electrode in Real Water - Amira Ghezal; Zina Fredj; Ammar Al‐Hamry; Marcos A. Gross; Leonardo G. Paterno; Mounir Ben Ali; Olfa Kanoun; Baljit Singh (Advanced Sensor Research)
Abstract This work presents a screen‐printed carbon electrode (SPCE) modified with iron oxide nanoparticles‐reduced graphene oxide (ION‐rGO) nanocomposite for the rapid and highly sensitive determination of nitrite in real water samples. The presence of both ION and rGO on the electrode surface enhances the sensing performance compared to the unmodified SPCE by reducing the charge transfer at the electrode/electrolyte interface. Under optimized conditions, it is demonstrated that the charge‐transfer resistance determined from electrochemical impedance spectroscopy (EIS) scales linearly with the logarithm of nitrite concentration. Due to its unique structure, the proposed nitrite sensor displays improved performance compared to our previous work, showing a linear range of 0.1 nM to 10 µM, a correlation coefficient of 0.9936, and an ultralow LOD of 17.3 pM. The results indicate that the modified electrodes possessed remarkable catalytic activity toward nitrite oxidation. Additionally, the ION‐rGO nanocomposite‐based sensor exhibited high sensitivity as well as good stability and reproducibility performance. The research findings demonstrate that the proposed sensor is a potential candidate for nitrite detection in real water sample analysis, which would be helpful in monitoring and protecting our global water resources.